Removal of Arabinose Substituents from Corn Pericarp Arabinoxylan - Tomoki Yoshida; Wahyu Dwianto; Yoichi Honda; Hiroshi Uyama; Jun-ichi Azuma (Masyarakat Peneliti Kayu Indonesia, 2013)
Partial acid hydrolysis of corn pericarp arabinoxylan (arabinose/xylose (A/X) ratio 0.35 and mean molecular weight of 53.6 × 103) was carried out at pH 1.0 for 1 6 h at 37 57 °C to remove arabinose substituents. The removal of arabinose could be described by regression analysis with the method of least squares. Following the regression profile, three kinds of desubstituted arabinoxylans having A/X ratios of 0.25, 0.12 and 0.03 with mean molecular weight values of 37.3 × 103, 15.6 × 103 and 7.2 × 103, respectively, could be prepared. All corn pericarp arabinoxylans were in the amorphous state and the film formability of the native state was lost after the partial acid hydrolysis.